2019
DOI: 10.1021/acs.inorgchem.9b01853
|View full text |Cite|
|
Sign up to set email alerts
|

(Cu)tet(Cr2–xSnx)octS4–ySey Spinels: Crystal Structure, Density Functional Theory Calculations, and Magnetic Behavior

Abstract: A new series of (Cu) tet [Cr 2−x Sn x ] oct S 4−y Se y compounds was prepared by solid-state reaction at high temperature. Determination of the crystal structures by single-crystal X-ray diffraction revealed that CuCr 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Figure 4 shows the spectra obtained for each of the phases, and in them, four bands are clearly observed; however, by fitting the spectra with Lorentzian functions, we can perform a more detailed analysis and identify five signals, which are located at the approximate frequencies of 130, 165, 230, 265 and 320 cm -1 . Table 1 summarizes the vibrations observed for the compounds reported in this work and others previously reported by our group for similar solid spinel-type solutions [3], [13].…”
Section: Raman Analysismentioning
confidence: 64%
See 2 more Smart Citations
“…Figure 4 shows the spectra obtained for each of the phases, and in them, four bands are clearly observed; however, by fitting the spectra with Lorentzian functions, we can perform a more detailed analysis and identify five signals, which are located at the approximate frequencies of 130, 165, 230, 265 and 320 cm -1 . Table 1 summarizes the vibrations observed for the compounds reported in this work and others previously reported by our group for similar solid spinel-type solutions [3], [13].…”
Section: Raman Analysismentioning
confidence: 64%
“…The normal spinel-type compounds crystallize in the 𝐹𝑑3 ̅ 𝑚 space group, corresponding to a face-centered cubic structure (fcc) that has an arrangement with a large unit cell, which contains eight units of the formula (8 cations A, 16 cations M and 32 anions X) [6,18]. The structure has 17 vibrational modes, of which five of them are active in Raman,  R = A 1g + E g + 3 F 2g [3], [13], [16][17][18][19].…”
Section: Raman Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, replacing metal ions in the octahedral or tetrahedral position with diamagnetic ions can alter the magnetic properties of CuCr2S4 and CuCr2Se4. In (Cu)tet[Cr2-xMx]octSe4 spinels, the substitutions of Cr by M (M = Zr, Sn) have indicated that M is present as a 4 + ion, and Cu as a diamagnetic Cu + ion [3,12]. For CuCr2S4, its physical properties can be understood if its charge distribution is assumed to be Cu + Cr 3+ Cr 4+ S4 8− ; thus, metallic conduction and ferromagnetism are ascribed to the double exchange between Cr 3+ and Cr 4+ [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…§ cell a parameter obtained from single-crystal analysis of CuCr1.0Sn1.0S2.1Se1.9 was 10.398(2) Å[12].…”
mentioning
confidence: 99%